Augmenting Sensor Performance with Machine Learning Towards Smart Wearable Sensing Electronic Systems. (19th January 2022) - Zhang, Songlin; Suresh, Lakshmi; Yang, Jiachen; Zhang, Xueping; Tan, Swee Ching
Abstract : Wearable sensing electronic systems (WSES) are becoming a fundamental platform to construct smart and intelligent networks for broad applications. Various physiological data are readily collected by the WSES, including biochemical, biopotential, and biophysical signals from human bodies. However, understanding these sensing data, such as feature extractions, recognitions, and classifications, is largely restrained because of the insufficient capacity when using conventional data processing techniques. Recent advances in sensing performance and system‐level operation quality of the WSES are expedited with the assistance of machine learning (ML) algorithms. Here, the state‐of‐the‐art of the ML‐assisted WSES is summarized with emphasis on how the accurate perceptions on physiological signals under different algorithms paradigm augment the performance of the WSES for diverse applications. Concretely, ML algorithms that are frequently implemented in the WSES studies are first synopsized. Then broad applications of ML‐assisted WSES with strengthened functions are discussed in the following sections, including intelligent physiological signals monitoring, disease diagnosis, on‐demand treatments, assistive devices, human–machine interface, and multiple sensations‐based virtual and augmented reality. Finally, challenges confronted for the ML‐assisted WSES are addressed. Abstract : Through collecting physiological data from the human bodies (i.e., biochemical, biopotential, and biophysical signals), smart wearable sensing electronic systems (WSES) are enabled as intelligent devices by machine learning algorithms for diverse applications, including healthcare, disease diagnosis and treatment, human–machine interfaces, and virtual/augmented reality.